Discourse Strategies and the Production of Prosody by Prelingually Deaf Adolescent Cochlear Implant Users. Issue 2 (March 2017) - Holt, Colleen M.; Yuen, Ivan; Demuth, Katherine
Abstract : Objectives: The purpose of this study is to assess the use of discourse strategies and the production of prosody by prelingually deaf adolescent users of cochlear implants (CIs) when participating in a referential communication task. We predict that CI users will issue more directives (DIRs) and make less use of information requests (IRs) in completing the task than their normally hearing (NH) peers. We also predict that in signaling these IRs and DIRs, the CI users will produce F0 rises of lesser magnitude than the NH speakers. Design: Eight prelingually deaf adolescent CI users and 8 NH adolescents completed a referential communication task, where participants were required to direct their interlocutor around a map. Participants were aged from 12.0 to 14.2 years. The mean age at implantation for the CI group was 2.1 years (SD 0.9). The use of IRs, DIRs, acknowledgments, and comments was compared between the two groups. The use and magnitude of fundamental frequency (F0) rises on IRs and DIRs was also compared. Results: The CI users differed from the NH speakers in how they resolved communication breakdown. The CI users showed a preference for repeating DIRs, rather than seeking information as did the NH speakers. A nonparametric Mann–Whitney U test indicated that the CI users issued more DIRs ( U = 8, p = 0.01), produced fewer IRs ( U = 13, p = 0.05) and fewer acknowledgments ( U = 5, p = 0.003) than their NH counterparts. The CI users also differed in how they used F0 rises as a prosodic cue to signal IRs and DIRs. The CI users produced larger F0 rises on DIRs than on IRs, a pattern opposite to that displayed by the NH speakers. An independent samples t -test revealed that the CI users produced smaller rises on IRs compared with those produced by the NH speakers [ t (12) = −2.762, p = 0.02]. Conclusions: The CI users differed from the NH speakers in how they resolved communication breakdown. The CI users showed a preference for repeating DIRs, rather than seeking information to understand their interlocutor's point of view. Their use of prosody to signal discourse function also differed from their NH peers. These differences may indicate a lack of understanding of how prosody is used to signal discourse modality by the CI users. This study highlights the need for further research focused on the interaction of prosody, discourse, and language comprehension.